The Number of Masses Celebrated Each Day in Hildemar of Corbie’s Expositio Regulae Sancti Benedicti - McGrane, Colleen Maura ca. 21. Jh. (Revue bénédictine, 2024)
Given that the Rule of Benedict provided only for Sunday Mass (Reg. Ben. 38,1-2 and A. de Vogüé, 1971), the number of Masses inserted into the daily monastic horarium by Carolingian monks determined to what extent the horarium had to be altered from its original intent. Recent scholarship suggests that the Expositio Regulae Sancti Benedicti of Hildemar of Corbie inserted two conventual Masses in addition to private Masses into the daily horarium. This article suggests that a close readingof the Hildemar commentary indicates that aside from Sundays and major feast days, Hildemar prescribed for only one conventual Mass daily. Only during Lent did priest-monks say two private Masses daily.